PENGARUH KEPEMIMPINAN DAN KOMPENSASI TERHADAP DISIPLIN KERJA PEGAWAI (Sensus Pada Perawat ASN RSUD Kabupaten Ciamis) - Titin Patimah; Nita Fauziah Oktaviani (LP2M Universitas Perjuangan Tasikmalaya, 2021)
This study aims to determine and analyze the influence of leadership and compensation on the work discipline of nurses partially and simultaneously. In this study, the sample was drawn using saturated sampling or census, namely all members of the population with a total of 159 ASN nurses at Ciamis District Hospital. Sources of data from secondary and primary. Data collection techniques: 1). field research (field research), namely by observation, interviews, and questionnaires (questionnaire) with a Likert scale, 2). library research, 3). internet research. This research consists of instrument testing with validity and reliability tests. Then descriptive testing was carried out using statistical testing by performing correlation analysis, path analysis, and hypothesis testing (t-test and f-test) using SPSS for Windows software. The results of the study concluded that leadership and compensation have a significant influence on work discipline in nurses at Ciamis District Hospital, either partially or simultaneously